Wykpić system. Historia pisma satyrycznego „Jaruzela” (1982–1989) - Wołk, Grzegorz (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article is a monograph on one of the most interesting satirical magazines published by the Solidarity underground after the imposition of martial law. The delegalization of the Independent Self-governing Trade Union Solidarity on December 13, 1981, forced contributing union activists into underground activity; its most noticeable outcome was the so-called second circulation. The opposition activists devoted their energy to the production of informational and political magazines. Still, other magazines were also created, including satirical titles such as “Jaruzela”. The article considers a broader context for the magazine’s history to showcase its specificity. The satirical initiatives of the opposition before the time of Solidarity, as well as trade union letters from 1980–1981, have proven that “Jaruzela” was not an ephemeral or unique phenomenon. On the other hand, it was one of the most interesting phenomena of the 1980s Polish second circulation. Compared to the underground as well as the official competition, the editorial quality of the magazine was high, and its specific sense of humor targeted towards a more educated recipient. The authors of the magazine, Tomasz Buchholtz and Jarosław Lindenberg, managed to run it from 1982 to 1989, when the political changes curtailed the second circulation phenomenon. The magazine’s other undisputed success was its reception by the opposition circles and people sympathizing with the Solidarity underground, as evidenced by reprints of drawings and texts from “Jaruzela” in other underground magazines, as well as the lasting and positive memory of the title among the members of the opposition.